2022
DOI: 10.1097/spc.0000000000000609
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare provider experiences during COVID-19 redeployment

Abstract: Purpose of reviewAmong the myriad traumatic impacts of COVID-19, the need for redeployment served as a significant stressor for healthcare providers (HCPs). This narrative review summarizes the current literature on HCP redeployment experiences and institutional support for staff, while proposing a theoretical approach to mitigating the negative impact on HCP mental health.Recent findingsRedeployment was a strong predictor of negative emotions in HCP during the initial stage of the COVID-19 pandemic, whereas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Step 3: Listen to Frontline Staff While it is always essential to ensure voices of frontline staff are heard, this becomes particularly crucial when addressing WPV in healthcare. WPV is a demoralizing issue contributing to undesirable patient outcomes, HCP burnout and high turnover rates, thus, making HCPs feel heard on this subject by their own organization can have a positive impact on staff engagement with the WPV QI process [31].…”
Section: Interpretation Systematic Framework To Address Wpv In Health...mentioning
confidence: 99%
“…Step 3: Listen to Frontline Staff While it is always essential to ensure voices of frontline staff are heard, this becomes particularly crucial when addressing WPV in healthcare. WPV is a demoralizing issue contributing to undesirable patient outcomes, HCP burnout and high turnover rates, thus, making HCPs feel heard on this subject by their own organization can have a positive impact on staff engagement with the WPV QI process [31].…”
Section: Interpretation Systematic Framework To Address Wpv In Health...mentioning
confidence: 99%
“…The exception is the reported gain of new research skills during the pandemic. Indeed, other studies have suggested that the concept of "benefit-finding", a process mainly described in cancer patients by which an individual identifies positive growth experiences resulting from trauma, can be applied to the experience of COVID-19 [17]. Overall these results suggest that while individuals are able to draw on reserves of internal motivations, institutions should support this feeling by incentivizing desired behaviors, and helping guide employees towards an understanding of the new skills and capabilities that may have been gained through a difficult experience.…”
Section: Plos Onementioning
confidence: 99%
“…As organizational change can induce uncertainty, anxiety and stress for staff leading to burnout [13] and as healthcare providers were already experiencing burnout before the pandemic [14,15], our goal was to minimize the stress created by implementing change. 1-2 different technologies were released every 4-6 weeks after smaller pilot testing with a smaller sample group [12].…”
Section: Planning and Implementing Digital Transitionmentioning
confidence: 99%